Investigating the Online Game-based and Group-Based Flipped Online Learning of Drug Abuse Prevention on Learning Achievement Among Grade 10 Students in Bangkok, Thailand - Srisiri, Sununta; Mootin, Songmongkorn (ACPES (ASEAN Council of Physical Education and Sport) in cooperation with Universitas Negeri Semarang (UNNES), 2021)
This study was examined the effect of the online Game-based learning versus the Group-Based Flipped Classroom online learning experiences about drug abuse prevention on the learning achievement among grade 10 students in Bangkok, Thailand. Classroom action research was implemented among grade 10 students at high school in Bangkok selected through purposive. Two comparable classrooms were assigned to either the online game-based learning or group-based flipped online learning for 2 weeks. The instruments employed in the study consisted of: (1) a flipped classroom model with online group investigation, (2) an online game-based model as individual learning, (3) the learning achievement—drug abuse prevention cognitive test. Independent t-test was analyzed to test the effectiveness of the two interventions. It revealed there was a significant difference in the learning achievement of drug abuse prevention given to those who were exposed to online game-based learning and those who were exposed to group-based flipped classroom online learning (t= 3.945, n1= 43, n2= 39, p= 0.000). From the study, high school students who were exposed to the online game-based learning performed better to those exposed to group-based flipped classroom online learning. Teachers are to encourage students to use individual learning to improve performance.